Chernobyl-Related Cancer and Precancerous Lesions: Incidence Increase Vs. Late Diagnostics - Sergei V. Jargin (SAGE Publishing, 2014)
The reported incidence of thyroid cancer in children and adolescents in Soviet Union before the Chernobyl accident was lower than in other developed countries. This is not clearly recognizable from the literature because comparisons of the high incidence figures 4 years after the accident and later have been made with those from the first years after the accident, when the registered incidence had already started to increase. Considering the low pre-accident registered incidence, there was an accumulated pool of undiagnosed thyroid tumors before the accident. The percentage of more advanced cancers, larger in size and less differentiated, was higher after the accident, when the pool of neglected cancers was diagnosed due to the screening and improved diagnostics. Some of these advanced tumors found by screening were interpreted as aggressive radiogenic cancers. The same tendency might be true also for other cancers, e.g. renal cell carcinoma. Furthermore, the screening-effect, false-positivity and registration of non-exposed patients as Chernobyl victims has obviously contributed to the registered incidence increase of malignancy.